Pelaksanaan Seleksi Perangkat Desa Sidomukti Kecamatan Jenawi Kabupaten Karanganyar dengan Sistem Computer Based Test (CBT) - Singgih Purnomo; Sopingi Sopingi (Pakis Journal Institute, 2024)
Sidomukti Village is a village located in Jenawi District, Karanganyar Regency, Central Java. This Community Service aims to carry out selection of village officials in Sidomukti Village, Jenawi District, Karanganyar Regency. The vacant village official position is Head Of Noyu Hamlet. The Village apparatus selection exams carried out include written exams and computer pratical exams in accordance with Karanganyar Regent regulation Number 81 of 2022 concerning Mechanisms for Appointing and Dismissing Village Apparatus. The result of the Community Service activities was the election of head of Noyu Hamlet, Sidomukti Village, Jenawi District, Karanganyar Regency, as stated in the Minutes of Selection of Sidomukti Village Apparatus, Jenawi District, Karanganyar Regency.